Virtual scientific events as spaces for reflection and learning - Veytia Bucheli, María Guadalupe (2024)
The objective of this article is to report the planning process of the event, its design, development, implementation and reflection of the lessons learned in the scientific event held in the context of the 20th Anniversary of the Bachelor's Degree in Education Sciences of the Autonomous University of State of Hidalgo during the COVID-19 pandemic period virtually. It was carried out through the Zoom platform where different scientific activities were developed such as: conferences, book presentations, workshops, discussions and forums. To evaluate the impact of the activities, an online questionnaire was administered to the participants. The results obtained reflect a positive evaluation of the event due to the different activities carried out, as well as the interest in continuing to generate spaces that allow listening to the experience of teachers, students, graduates and national and international guests who address topics related to Sciences. of Education.